Lima Tokoh Pahlawan Nasional dari Muhammadiyah di Indonesia - Suwarno, Suwarno (SOSIOHUMANIKA, 2008)
ABSTRACT: The study of heroes is very important to learn, especially for young generation. It is not essentially intended to cult the individuals due to those heroesâ grandeur, but to implant national awareness and pride. The awareness to respect othersâ service and sacrifice is an expression of national awareness and pride, as frequently stated by Bung Karno that the big nation is nation that appreciate the service of its heroes. This paper is aimed to describe five figures of heroes from Muhammadiyah. They are K.H. Ahmad Dahlan (1868-1923), Nyi Ahmad Dahlan (1872-1946), K.H. Fachruddin (1890-1929), K.H. Mas Mansur (1896-1946) and General Sudirman (1916-1950). The focus of this paper is a short biography of the five figures and their roles played in national context. Those five Muhammadiyah figures are very reasonable to be determined as national heroes through their roles they played and their contribution not only for Moslem but also for our people. K.H.A Dahlan (1868-1923) was a pioneer in advancing education, who integrated religion education and general science. Nyi Ahmad Dahlan (1872-1946) had given higher contribution, not only for developing Muhammadiyah but also for empowering and advancing Muslimah group, especially through Aisyiyah organization. K.H. Fachruddin (1890-1929) had important roles in external Muhammadiyah struggle. K.H. Mas Mansur (1896-1946) was the first figure of Muhammadiyah, who had higher social and political influence in Indonesian independence movement struggle. And General Sudirman (1916-1950) was a Muhammadiyah figure, who was active in military, and had been national figure, who was reasonable to be followed as uswatun hasanah (role model) because of his modesty, bravery and sincerity in fighting for his country.Key words: Muhammadiyah figures, national heroes, and its roles and contributions for Indonesian and character building.About the Author: Drs. Suwarno, M.Si. adalah Dosen pada Program Studi Pendidikan Sejarah FKIP Universitas Muhammadiyah Purwokerto (UMP) di Jawa Tengah. Beliau dilahirkan di Purwokerto, pada tanggal 9 Agustus 1966. Menyelesaikan pendidikan Sarjana (Drs.) dari IKIP (Institut Keguruan dan Ilmu Pendidikan) Yogyakarta tahun 1990; dan Magister Sosial (M.Si.) dari UGM (Universitas Gadjah Mada) Yogyakarta tahun 2000. Beliau banyak melakukan penelitian yang berkenaan dengan agama dan masyarakat Islam di Indonesia. Beliau juga menulis buku, di antaranya adalah: Muhammadiyah sebagai Oposisi (Yogyakarta: UII Press, 2001). Untuk kepentingan akademik, beliau boleh dihubungi dengan alamat kantor: Fakultas Keguruan dan Ilmu Pendidikan UMP, Jalan Raya Dukuh Waluh, PO Box 202, Purwokerto 53182, Jawa Tengah, Indonesia. Emel: aspensi@yahoo.comHow to cite this article? Suwarno. (2008). âLima Tokoh Pahlawan Nasional dari Muhammadiyah di Indonesiaâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.1, No.2 [November], pp.311-330. Bandung, Indonesia: Minda Masagi Press, UPI Bandung, and UMS Kota Kinabalu, Malaysia, ISSN 1979-0112.Chronicle of the article: Accepted (August 17, 2008); Revised (October 5, 2008); and Published (November 20, 2008).